Modelling concept for organizational goals conformance using ontology - Tengku Adil Tengku Izhar; Torab Torabi; M. Ishaq Bhatti (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
We propose a modelling concept for the organizational goals as a tool to evaluate organization data conformance in relation the organization goal. We suggest that this model is important in assisting the organization to utilize the organization data and information from the vast amount of data for decision making which will be in line with the organization's goals. We develop this model based on organizational goal elements such as the main goal, sub-goals, actions and tasks. A formal ontology is developed to specific role between the organization goal elements. We develop a metric model in order to interpret organization data. We apply a case study to evaluate our model development, metric development and relationship development. Overall, the main contribution of this paper is to propose a conceptual model that seeks to support the evaluation of organization data based on organization goal elements in the achievement of the organization's goals.
Keywords: 650; Action; Data; Data usage; Goals; Goal tree model; Organization; Ontology; Sub-goal; Task